Comparative study of physico-chemical properties of some molecules from Khaya Grandifoliola plant - E. R. Atangana Nkene; R. A. Yossa Kamsi; H. Zangue Adjia; M. T. Ottou Abe; A. Teyou Ngoupo; J. M. B. Ndjaka (Scientific Reports)
Abstract The three molecular compounds: A (17-epi-methyl-6-hydroxylangolensate), B (7-deacetoxy-7-oxogedunin) and C (7-deacetoxy-7R-hydroxygedunin) isolated from Khaya Grandifoliola, a plant of the Meliaceae family, able to protect the normal human hepatocyte cell line against paracetamol-induced hepatotoxicity were studied using HF and DFT methods. It appears from this study that compound A has the greatest capacity of donating charges while compound B, which is the most reactive compound according to the HOMO-LUMO energy gap, has a greater capacity to accept charges. From the calculation of certain donor-acceptor parameters, it comes out that compound C is the most easily oxidizable substance and therefore the most effective free radical scavenger. Of the three molecular compounds, A is the best antioxidant while B is the best antireductant. From the values ​​obtained for compounds A, B and C, we concluded that these compounds are better antioxidants than β-carotene and better antireductants than vitamins A, C and E. Compounds A, B, and C are less efficient electron acceptors than fluorine and more efficient electron donors than Na. The calculation of certain thermodynamic parameters shows that, the molecular compounds studied can easily bind to a biomolecular complex. UV-vis spectrum analysis shows that the maximum peaks are located in the UV region between 230 and 356 nm. The nonlinear optical parameters along with vibrational frequencies of these compounds were calculated and compared.